Prospective unmasked randomized evaluation of the iStent inject (®) versus two ocular hypotensive agents in patients with primary open-angle glaucoma - Fea, Antonio M.; Belda, Jose I.; Rekas, Marek; Jünemann, Anselm; Chang, Lydia; Pablo, Luis; Voskanyan, Lilit; Katz, L. Jay (Clinical Ophthalmology, 2014)
The purpose of this study was to compare outcomes of subjects with open-angle glaucoma (OAG) not controlled on one medication who underwent either implantation of two iStent inject (®) trabecular micro-bypass devices or received medical therapy consisting of a fixed combination of latanoprost/timolol.Of 192 subjects who qualified for the study and were enrolled, 94 were randomized to surgery with implantation of two iStent inject(®) devices in the treated eye and 98 to receive medical therapy.At the month 12 visit, 94.7% of eyes (89/94) in the stent group reported an unmedicated intraocular pressure (IOP) reduction of >=20% versus baseline unmedicated IOP, and 91.8% of eyes (88/98) in the medical therapy group reported an IOP reduction >=20% versus baseline unmedicated IOP. A 17.5% between-group treatment difference in favor of the iStent inject group was statistically significant (P=0.02) at the >=50% level of IOP reduction. An IOP <=18 mmHg was reported in 92.6% of eyes (87/94) in the iStent inject group and 89.8% of eyes (88/98) in the medical therapy group. Mean (standard deviation) IOP decreases from screening of 8.1 (2.6) mmHg and 7.3 (2.2) mmHg were reported in the iStent inject and medical therapy groups, respectively. A high safety profile was also noted in this study in both the iStent inject and medical therapy groups, as measured by stable best corrected visual acuity, cup-to-disc ratio, and adverse events.These data show that the use of iStent inject is at least as effective as two medications, with the clinical benefit of reducing medication burden and assuring continuous treatment with full compliance to implant therapy as well as having a highly favorable safety profile.
EVALuna2:21209